The characteristic traits of David Copperfield in “David Copperfield” by Charles Dickens = NHỮNG ĐẶC ĐIỂM CỦA DAVID COPPERFILED TRONG TÁC PHẨM “DAVID COPPERFIELD” CỦA CHARLES DICKENS - Nguyễn, Thị Hà (2021)
The study focuses on analyzing the characteristic traits of David Copperfield in the novel “David Copperfield” by Charles Dickens. This graduation paper involves two main parts: part A: introduction, and part B: development. Part A is the introduction about the way that the study is carried out. Rationale, aims, objectives, significant of the study, scope of the study, and methodology are all shown. Part B of the study contains five chapters. Chapter one is about literature review of the graduation paper. In chapter two, the image of English literature in the 19th century is briefly shown. Chapter three tells about some outstanding information about Charles Dickens and the novel “David Copperfield”. Chapter four is the main part of the study which discusses the characteristic traits of David Copperfield when he was small until he became a mature man. Chapter five introduces some remarks on Dickens’ writing styles in the novel. The final part is the conclusion of the study.